Transparência ativa e passiva nos institutos federais de ensino superior à luz da Lei de Acesso à Informação - Lima, Franciane Leal (2023)
For a long time, the secrecy of information was the rule for processing data of interest to society. However, as democratic governments matured, access to information and transparency of public information gained the status of a fundamental right and became part of the list of rights to be enforced by the state. In Brazil, access to information and transparency have become tools at the service of society, in order to allow it to participate more actively and forcefully in the running of public affairs, through inferences of control, monitoring and inspection. To this end, bodies such as the Office of the Comptroller General have been created to monitor and supervise compliance with legislation on access to information and public transparency by the Federal Public Administration. With this in mind, this study sought to analyze the level of active and passive transparency of the 38 Federal Institutes of Higher Education, which are autarchies of the Federal Government, created by Law 11.892/2008. To this end, the study presented notions of access to information, public transparency and open government, as well as the role of the Office of the Comptroller General in monitoring and overseeing the legal dictates of access to information and transparency, mainly in relation to Law 12.527.2011 and Decree 7.724/2012. Finally, it presented a ranking of the Federal Institutes' active and passive transparency levels. This is an applied, descriptive study with a qualitative approach. In terms of technical data collection procedures, it was characterized as a survey. The research universe included the 38 Federal Institutes of Higher Education in Brazil, with a census-type sample. The instrument used for data collection was developed by Diógenes (2021), based on the Transparent Brazil Scale - EBT 360º methodology of the Office of the Comptroller General. The results of the survey showed that around 76.31% of the Federal Institutes achieved an average score of 89.18 for public transparency. It was also revealed that the three most widely disseminated information topics were Actions and Programs, Income and Expenditure, and Tenders and Contracts. The survey showed that 94.7% of federal institutes responded to requests for access to information, demonstrating that most of them comply with requests for information. Overall, it is clear that the federal institutes have sought to comply with the legal dictates of access to information and public transparency.